The Image of Germany in Thomas Mann’s Lecture, "Germany and the Germans," and in its Translations - TEMPEL, Małgorzata (Transfer. Reception Studies, 2017)
In his 1945 lecture, "Germany and the Germans" given in Washington D.C., Thomas Mann makes an attempt to investigate the roots of national socialism and solve the "riddle" of the German nature. In Poland this lecture is one of the texts that has influenced the way in which the western neighbour has been perceived, and at the same time, it has played a role as an intermediary in the Polish-German cultural dialogue. This intermediary function is performed naturally and particularly by translation, which - as it is postulated by Göttinger Sonderforschungsbereich Die literarische Übersetzung - leads toward the rapprochement of cultures. The article offers an analysis of how the original image of Germany painted in the lecture by Thomas Mann was interpreted and conveyed to the Polish reader through three different translations.